The way forward to overcome challenges and drawbacks of AI - Jena, Madhab Chandra; Mishra, Sarat Kumar; Moharana, Himanshu Sekhar (Computing and Artificial Intelligence, 2024)
Artificial Intelligence (AI) is revolutionizing various sectors, including healthcare, finance, and education, yet its rapid adoption is accompanied by significant challenges and drawbacks that warrant urgent attention. This manuscript explores key issues such as job displacement, algorithmic bias, privacy concerns, and environmental impacts, presenting a comprehensive overview of the multifaceted challenges associated with AI integration. Utilizing a robust methodology that includes literature reviews, thematic analysis, and expert interviews, the study identifies critical barriers to effective AI implementation. Furthermore, it proposes strategic recommendations aimed at mitigating these challenges, emphasizing the need for reskilling initiatives, ethical frameworks, and collaborative regulatory efforts. The findings underscore the importance of a balanced approach that maximizes AI benefits while addressing its inherent risks, ultimately paving the way for a more equitable and sustainable technological future.